An Evaluation and Oversight Framework for Participatory Budgeting in Boston. - Clark, Kimberly.; Desloges, Arthur.; Emmanuel, Gideon.; Shively, Johnny.; Syed, Ayesha. (Tufts University. Tisch Library., 2023)
2022 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: Center for Economic Democracy (CED)